A Narrative Review of the Efficacy of Long COVID Interventions on Brain Fog, Processing Speed, and Other Related Cognitive Outcomes - Bryana Whitaker-Hardin; Keith M. McGregor; Gitendra Uswatte; Kristine Lokken (Biomedicines)
In the years following the global emergence of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), or COVID-19, researchers have become acutely aware of long-term symptomology associated with this disease, often termed long COVID. Long COVID is associated with pervasive symptoms affecting multiple organ systems. Neurocognitive symptoms are reported by up to 40% of long COVID patients, with resultant effects of loss of daily functioning, employment issues, and enormous economic impact and high healthcare utilization. The literature on effective, safe, and non-invasive interventions for the remediation of the cognitive consequences of long COVID is scarce and poorly described. Of specific interest to this narrative review is the identification of potential interventions for long COVID-associated neurocognitive deficits. Articles were sourced from PubMed, EBSCO, Scopus, and Embase following Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Articles published between the dates of January 2020 and 30 June 2024 were included in the search. Twelve studies were included in the narrative review, including a feasibility study, a pilot study, a case series, a case study, and an observational study, in addition to three randomized clinical trials and four interventional studies. Overall, treatment interventions such as cognitive training, non-invasive brain stimulation therapy, exercise rehabilitation, targeted pharmacological intervention, and other related treatment paradigms show promise in reducing long COVID cognitive issues. This narrative review highlights the need for more rigorous experimental designs and future studies are needed to fully evaluate treatment interventions for persistent cognitive deficits associated with long COVID.